Analysis of the Suitability of Infant Food Composition in “Babyfood X” in Compliance with Halal Certification Regulations: Analisis Kesesuaian Komposisi Makanan Bayi di “Babyfood X” terhadap Kepatuhan Regulasi Sertifikasi Halal - Rafdiansyah, Muhammad Ainur; Nurbaya, Syarifa Ramadhani; Handayani, Puspita; Azara, Rima (Journal of Halal Lifestyle and Sustainability, 2025)
This article aims to analyze the suitability of the composition of baby food produced by "Babyfood X" to comply with halal certification regulations in Indonesia. This research is important considering that baby food is a consumer product that is very sensitive to safety aspects and compliance with sharia principles, especially in terms of halal raw materials and production processes. The methodology in this research is observation, interviews with “Babyfood X", literature study, and qualitative data analysis. This article shows that there are variations in the menu produced every day. The menu served is varied so it doesn't get boring because the majority of target consumers are babies aged 6 months and over. The baby food produced certainly pays attention to the right composition and nutrition, and also complies with halal food regulations, so it is safe for consumption for babies.